The rise and fall of major royal jelly proteins during a honeybee (Apis mellifera) workers' life. Issue 15 (5th July 2019) - Dobritzsch, Dirk; Aumer, Denise; Fuszard, Matthew; Erler, Silvio; Buttstedt, Anja
Abstract: The genome of the western honeybee ( Apis mellifera ) harbors nine transcribed major royal jelly protein genes ( mrjp1‐9 ) which originate from a single‐copy precursor via gene duplication. The first MRJP was identified in royal jelly, a secretion of the bees' hypopharyngeal glands that is used by young worker bees, called nurses, to feed developing larvae. Thus, MRJPs are frequently assumed to mainly have functions for developing bee larvae and to be expressed in the food glands of nurse bees. In‐depth knowledge on caste‐ and age‐specific role and abundance of MRJPs is missing. We here show, using combined quantitative real‐time PCR with quantitative mass spectrometry, that expression and protein amount of mrjp1‐5 and mrjp7 show an age‐dependent pattern in worker's hypopharyngeal glands as well as in brains, albeit lower relative abundance in brains than in glands. Expression increases after hatching until the nurse bee period and is followed by a decrease in older workers that forage for plant products. Mrjp6 expression deviates considerably from the expression profiles of the other mrjps, does not significantly vary in the brain, and shows its highest expression in the hypopharyngeal glands during the forager period. Furthermore, it is the only mrjp of which transcript abundance does not correlate with protein amount. Mrjp8 and mrjp9 show, compared to the other mrjps, a very low expression in both tissues. Albeit mrjp8 mRNA was detected via qPCR, the protein was not quantified in any of the tissues. Due to the occurrence of MRJP8 and MRJP9 in other body parts of the bees, for example, the venom gland, they might not have a hypopharyngeal gland‐ or brain‐specific function but rather functions in other tissues. Thus, mrjp1‐7 but not mrjp8 and mrjp9 might be involved in the regulation of phenotypic plasticity and age polyethism in worker honeybees. Abstract : Major royal jelly proteins of honeybees are unregulated in hypopharyngeal glands and brains of brood‐feeding nurse bees compared to foragers and freshly hatched bees.